Management of captive Passeriformes in eastern Amazonia: the bird keepers - Silva, Samantha; Braga, Brenda; da Silva Costa, Juliane; da Costa Ribeiro, Marília; Lima Cardoso, Deise; Gilberto Zangeronimo, Márcio; Chaves Baía Júnior, Pedro; Anelie de Araújo Guimarães, Diva (Ethnobiology and Conservation, 2023)
The interactions between avifauna and the environment, including relationships with humans and their role in cultural practices, are part of ethnoornithological studies. The main objective of this study was to describe the ex situ management of passerines by bird keepers for recreational and commercial purposes in a municipality in the Brazilian Amazon. Semi-structured interviews were conducted with 62 farmers who had 279 wild birds belonging to 23 species in captivity. These animals were kept in cages of different sizes. The birds’ diets were obtained from specialized commercial stores and offered daily to the animals according to age group and reproductive stage. The animals were kept in environments with good air flow, and the cages were cleaned, and the water was changed daily. Worming of birds was a routine practice, but infestations and some diseases were noted. Medications for treatment were obtained from local specialized stores. The reproductive management of passerine birds, especially Sporophila angolensis and Sporophila maximiliani, was performed by only three breeders. The results provide relevant empirical knowledge about the ex situ management of passerines, which is part of local cultural habits. However, this study indicates that there may be negative effects of maintaining these birds in captivity, such as the capture of free-ranging wild animals. Socio-educational measures are necessary to improve awareness of the sustainable use of environmental resources and encourage legalized breeding of passerines to help conserve the species.